The Validity and Reliability of Career Readiness Instruments for Vocational High School Students - Diajeng Retno Kinanti Putri; Mamat Supriatna; Eka Sakti Yudha (Psychocentrum Review, 2022)
Career readiness is an important key that must be possessed by students before entering the business world/industrial world. In an effort to understand the level of student career readiness, a valid and reliable instrument is needed. So the purpose of this research is to test the validity and reliability of the instrument. This research uses a quantitative approach with instrument development and validation methods. The sample in this study was 344 Vocational High School students in the Province of East Java Indonesia. Data analysis using Winstep. Based on the results of the winstep program analysis of the 60 items developed, 3 items were not used because they did not meet the three item validity standards. While the reliability in special category. Based on the results of unidimensional, each dimension can measure the variable properly and is not influenced by other factors that cause changes in the results instrument From several analysis results, it can be concluded that the career readiness instrument can be used to measure the career readiness of SMK students.